Proceedings of the Twenty-Fifth Annual ACM Symposium on Parallelism in Algorithms and Architectures 2013
DOI: 10.1145/2486159.2486178
|View full text |Cite
|
Sign up to set email alerts
|

Parallel rotor walks on finite graphs and applications in discrete load balancing

Abstract: We study the parallel rotor walk process, which works as follows: Consider a graph along with an arbitrary distribution of tokens over its nodes. Every node is equipped with a rotor that points to its neighbours in a fixed circular order. In each round, every node distributes all of its tokens using the rotor. One token is allocated to the neighbour pointed at by the rotor, then the rotor moves to the subsequent neighbour, and so on, until no token remains.The process can be considered as a deterministic analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…Friedrich et al [15] proposed the BED algorithm for load balancing, which uses some extra information in the previous time, and they gave O(d 1.5 ) for hypercube and O(1) for constantdimensional tori. Akbari and Berenbrink [1] discussed the relation between the BED algorithm and the rotorrouter model, and gave the same bounds for a rotorrouter model. Berenbrink et al [6] investigated about cumulatively fair balancers algorithms, which includes the rotor-router model, and gave an upper bound…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Friedrich et al [15] proposed the BED algorithm for load balancing, which uses some extra information in the previous time, and they gave O(d 1.5 ) for hypercube and O(1) for constantdimensional tori. Akbari and Berenbrink [1] discussed the relation between the BED algorithm and the rotorrouter model, and gave the same bounds for a rotorrouter model. Berenbrink et al [6] investigated about cumulatively fair balancers algorithms, which includes the rotor-router model, and gave an upper bound…”
Section: Introductionmentioning
confidence: 88%
“…Deterministic random walks [10,9,13,8,23,22,27] may be used as a substitute for Markov chains, for the purpose. Deterministic random walk Deterministic random walk is a deterministic process analogous to a (multiple) random walk 1 . A configuration χ (t) ∈ Z V ≥0 of M tokens distributed over a (finite) vertex set V is deterministically updated from time t to t + 1 by routers equipped on vertices.…”
Section: Introductionmentioning
confidence: 99%
“…As the number of agents k increases, the speed-up of the rotor-router with Table 1 The cover time of the multi-agent roter-router on the ring compared to multiple random walks (for k < n 1 …”
Section: As θ(N/k)mentioning
confidence: 99%
“…The structural properties of the distribution of tokens for a rotor-router system on the 2-dimensional grid were considered by Doerr and Friedrich [9]. Akbari and Berenbrink [2] proved an upper bound of O(log 3/2 n) on the load-balancing discrepancy for hypercubes, and for tori of constant dimensions, they showed that the discrepancy is bounded by a constant. For general d-regular graphs, a bound of O(d log n/µ) on the discrepancy of the rotor-router mechanism with respect to continuous diffusion follows from the general framework of [18], where µ is the eigenvalue gap of the graph, under the assumption that a sufficient number of self-loops are present at each node of the graph.…”
Section: Related Workmentioning
confidence: 99%